Media management activity of Zhanuzak Zhanibekov - Ibrayeva Э.Е.; Kylychbaeva Э. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
This article discusses the editorial work of the activist “Alash” Zhanibekov Zhanuzak Alzhanuly in the newspaper “Kedey”, published in Aktobe from 1926 to 1929. As the leader, the strategic work of Zhanuzak Alzhanuly will be considered, aimed at the effective coordination of the editorial work, determining the demand of the newspaper audience, establishing feedback with the public, as well as increasing the circulation of the publication. At the same time, the organizational aspect is the newspaper’s editor-organization of the work of journalists in the regions, informing about the country, determining the thematic focus of the upcoming number of publications. The managerial skills of «Alash» figure Zhanuzak Zhanibekov in managing the newspaper «Kedey» are formulated and documented by specific scientific facts and historical figures. The article scientifically analyzes and studies statistical data from archival materials, which was taken from the original files of the newspaper «Kedey».